Mucinous cystadenoma of ovary: are mammoths really extinct? - Sheregar, Namrita C.; Wani, Reena J. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
The most common ovarian tumours are epithelial tumours. 80% of all tumours are benign, 10% borderline and 10% are malignant. Mucinous tumours represent 8-10% of the epithelial tumours; they may reach enormous size filling the entire abdominal cavity. We report here a case of a huge benign mucinous cystadenoma in a 57-year-old female. Ultrasound and MRI scan showed a large left ovarian cyst. CA-125 was 132 IU/ml. She underwent total abdominal hysterectomy and bilateral salpingo-opherectomy with appendicectomy and infracolic omentectomy. Her post-operative course was unremarkable.